Computer use in educational activities by students with ADHD. - Bolic, Vedrana; Lidström, Helene; Thelin, Nils; Kjellberg, Anette; Hemmingsson, Helena (Scandinavian Journal of Occupational Therapy, 2013)
Aim: The aim of this study was to investigate computer use in educational activities by students with attention deficit hyperactivity disorder (ADHD) in comparison with that of students with physical disabilities and students from the general population. Methods: The design of the study was cross-sectional with group comparison. Students with ADHD ( n = 102) were pair-matched in terms of age and sex with students with physical disabilities and students from the general population ( n = 940) were used as a reference group. Results: The study showed that less than half of the students with ADHD had access to a computer in the classroom. Students with ADHD reported significantly less frequent use of computers for almost all educational activities compared with students with physical disabilities and students from the general population. Students with ADHD reported low satisfaction with computer use in school. In addition, students with ADHD reported a desire to use computers more often and for more activities in school compared with students with physical disabilities. Conclusions: These results indicate that occupational therapists should place more emphasize on how to enable students with ADHD to use computers in educational activities in school.